Hiding in the howardites: Unequilibrated eucrite clasts as a guide to the formation of Vesta's crust - Mayne, Rhiannon G.; Smith, Samantha E.; Corrigan, C. M. (Meteoritics & planetary science, 2016)
204 howardites in the National Meteorite Collection at the Smithsonian were examined for the presence of fine‐grained eucrite clasts, with the goal of better understanding the formation of the uppermost crust of asteroid 4Vesta. Eight clasts were identified and characterized in terms of their textures and mineral chemistry, and their degree of thermal metamorphism was assessed. The paucity of fine‐grained eucrites, both within the unbrecciated eucrites and as clasts within the howardites, suggests that they originate from small‐scale units on the surface of Vesta, most likely derived from partial melting. Six of the eight clasts described were found to be unequilibrated, meaning that they preserve their original crystallization trends. The vast majority of eucrites are at least partially equilibrated, making these samples quite rare and important for deciphering the petrogenesis of the vestan crust. Biomodal grain populations suggest that eucrite melts often began crystallizing pyroxene and plagioclase during their ascent to the surface, where they were subject to more rapid cooling, crystallization, and later metasomatism. Pyroxene compositions from this study and prior work indicate that the products of both primitive and evolved melts were present at the vestan surface after its formation. Two howardite thin sections contained multiple eucrite composition clasts with different crystallization and thermal histories; this mm‐scale diversity reflects the complexity of the current day vestan surface that has been observed by Dawn.